Building a multisystemic understanding of societal resilience to the COVID-19 pandemic. Issue 7 (22nd July 2021) - Wernli, Didier; Clausin, Mia; Antulov-Fantulin, Nino; Berezowski, John; Biller, Nikola; Blanchet, Karl; Böttcher, Lucas; Burton-Jeangros, Claudine; Escher, Gérard; Flahault, Antoine; Fukuda, Keiji; Helbing, Dirk; et al.
Abstract : The current global systemic crisis reveals how globalised societies are unprepared to face a pandemic. Beyond the dramatic loss of human life, the COVID-19 pandemic has triggered widespread disturbances in health, social, economic, environmental and governance systems in many countries across the world. Resilience describes the capacities of natural and human systems to prevent, react to and recover from shocks. Societal resilience to the current COVID-19 pandemic relates to the ability of societies in maintaining their core functions while minimising the impact of the pandemic and other societal effects. Drawing on the emerging evidence about resilience in health, social, economic, environmental and governance systems, this paper delineates a multisystemic understanding of societal resilience to COVID-19. Such an understanding provides the foundation for an integrated approach to build societal resilience to current and future pandemics.